Re-defining efficiency of feed use by livestock - J.M. Wilkinson (Animal, 2011)
Livestock, particularly ruminants, can eat a wider range of biomass than humans. In the drive for greater efficiency, intensive systems of livestock production have evolved to compete with humans for high-energy crops such as cereals. Feeds consumed by livestock were analysed in terms of the quantities used and efficiency of conversion of grassland, human-edible (‘edible’) crops and crop by-products into milk, meat and eggs, using the United Kingdom as an example of a developed livestock industry. Some 42 million tonnes of forage dry matter were consumed from 2008 to 2009 by the UK ruminant livestock population of which 0.7 was grazed pasture and 0.3 million tonnes was conserved forage. In addition, almost 13 million tonnes of raw material concentrate feeds were used in the UK animal feed industry from 2008 to 2009 of which cereal grains comprised 5.3 and soyabean meal 1.9 million tonnes. The proportion of edible feed in typical UK concentrate formulations ranged from 0.36 for milk production to 0.75 for poultry meat production. Example systems of livestock production were used to calculate feed conversion ratios (FCR – feed input per unit of fresh product). FCR for concentrate feeds was lowest for milk at 0.27 and for the meat systems ranged from 2.3 for poultry meat to 8.8 for cereal beef. Differences in FCR between systems of meat production were smaller when efficiency was calculated on an edible input/output basis, where spring-calving/grass finishing upland suckler beef and lowland lamb production were more efficient than pig and poultry meat production. With the exception of milk and upland suckler beef, FCR for edible feed protein into edible animal protein were >1.0. Edible protein/animal protein FCR of 1.0 may be possible by replacing cereal grain and soyabean meal with cereal by-products in concentrate formulations. It is concluded that by accounting for the proportions of human-edible and inedible feeds used in typical livestock production systems, a more realistic estimate of efficiency can be made for comparisons between systems.